Distributed Fault Estimation Observer Design With Adjustable Parameters for a Class of Nonlinear Interconnected Systems - Zhang, Ke; Jiang, Bin; Shi, Peng (IEEE transactions on cybernetics, 2019)
In this paper, a new distributed fault estimation observer with adjustable parameters is designed for a class of nonlinear interconnected systems. The presented fault estimator consists of proportional and integral terms to improve the accuracy of fault estimation. The observer gain matrices of the proposed fault estimation scheme for the underlying systems are calculated based on robust {\mathcal {L}_{2}-\mathcal {L}_{2}} and {\mathcal {L}_{2}-\mathcal {L}_∞ } performance. The proposed method achieves a lower performance level in the aspect of quantitative analysis compared with existing fault estimation approaches. A simulation example is provided to demonstrate the effectiveness of the new design method.